Humanistic Counselling as a Mediation Model for Reducing Learning Disengagement - Nur Nafisa Salsabila; Devi Mariatul Qiptiah (Journal of General Education and Humanities, 2026)
Learning disengagement among Indonesian school learners reflects a gradual breakdown of internal learning connections, involving the loss of personal meaning in learning, prolonged emotional saturation, self-doubt, and weakened psychological attachment to the school environment. This study conceptualises humanistic counselling as a mediating psychological process that restores students’ self-systems before behavioural engagement reappears. Using a qualitative design oriented to conceptual model development and analyzed through thematic synthesis, the research integrates core humanistic principles, including unconditional acceptance, empathic exploration, and reflective, non-directive dialogue, as internal enablers of learner recovery. The study formulates the Humanistic Counselling Mediation Pathway Model, identifying key psychological mediators, including reconstructed learning meaning, improved self-concept, emotional clarity, and renewed academic belonging. These internal processes are presented as antecedent mechanisms that logically precede the reduction of avoidance and withdrawal behaviours, allowing engagement indicators to return as behavioural consequences rather than as direct enforcement. The model offers an innovative contribution by explaining how engagement restoration is driven by intrapersonal psychological reconstruction, thereby strengthening the scientific narrative of counselling not merely as responsive support but as a preparatory transformation mechanism within Indonesian school behavioural learning contexts.